The Impact of Organizational and Situational Factors on the Relationship Between Disclosure Triangle Elements and Auditors’ Whistleblowing Motivation - Akbari, Zahra; Aghaei chadegani, Arezoo; Kamali, Ehsan (International Journal of Innovation Management and Organizational Behavior (IJIMOB), 2025)
Objective: This study aims to investigate the impact of organizational and situational factors on the relationship between disclosure triangle elements and internal auditors’ whistleblowing motivation. Methodology: The research employs a descriptive survey method, using a cross-sectional design and structural equation modeling to analyze data collected from a sample of 384 internal auditors through a questionnaire. Findings: The results reveal that the disclosure triangle elements, specifically opportunity and rationalization, positively influence whistleblowing motivation, while pressure does not have a significant effect. Additionally, organizational and situational factors do not moderate the relationship between disclosure triangle elements and whistleblowing motivation. Conclusion: Whistleblowing motivation is significantly driven by opportunity and rationalization, but organizational and situational factors fail to exert a moderating influence, emphasizing the need for ethical support and rational justification mechanisms within organizations to encourage whistleblowing behavior.